Conocimientos y prácticas de Leishmaniasis en la población expuesta de los cantones Chinchipe y Palanda. - Cabrera Cabrera, Katherine Lourdes (2018)
Leishmaniasis” is an unpleasant infection caused by flagellated protozoa of the genus “Leishmania” whose manifestations can be called cutaneous, mucocutaneous or visceral be contingent on the species to which the person is uncovered. The current research: KNOWLEDGE AND PRACTICES OF LEISHMANIASIS IN THE EXPOSED POPULATION OF THE PALANDA AND CHINCHIPE CANTONES, targeted to launch the knowledge and practices, which are being used by the population uncovered to “Leishmaniasis” from “Palanda” and “Chinchipe” cantons. This research project was settled with quantitative and qualitative approaches, 101 inhabitants were surveyed, locating the following result: 100% of the participating population which was surveyed knows that it is “Leishmanniasis”; It is correspondingly determined that the practices carried out in the presence of “Leishmania” is the usage of awnings with 77.22% and the abolition of water deposits with 68.31%; likewise in the forms of treatment it was gained as consequences that 71.28% of the population goes to a Health House and 51.48% makes the topical application of plants of the place; and in relation to the place where the person goes in case of suffering or having suffered the sickness is the Health Centre with 81.18%. The deduction is that the total population has awareness and understating about “Leishmaniasis”, which displays that the participants know what they practice doing before it. Keywords: Exposed population, knowledge, practices, sociodemographyc